Decentralization and Corruption: Policy and Legal Study on the Effectiveness of Local Financial Oversight - Candra, Edi; Tjenreng, M.B. Zubakhrum (Universitas Muhammadiyah Tangerang, 2025)
Decentralization in Indonesia aims to enhance the autonomy and efficiency of local governments in managing finances and public services. However, in practice, decentralization also creates opportunities for budget misappropriation and corruption due to weak oversight systems. This study analyzes the effectiveness of legal policies in local financial oversight using a juridical-normative approach and compares the implementation in regions with high levels of corruption and those with more effective oversight mechanisms. The analysis reveals that although regulations such as Law No. 23 of 2014 on Regional Government and Law No. 17 of 2003 on State Finance establish principles of transparency and accountability, their implementation faces challenges, including weak inter-agency coordination, political interference, and limited human resources. Efforts to enhance transparency through e-budgeting and e-procurement have been introduced but remain partially effective due to technical and infrastructure-related issues. A comparative study with South Korea and Finland demonstrates that the success of local financial oversight relies heavily on the integration of digital systems, the independence of oversight institutions, and a strong culture of governance integrity. Therefore, Indonesia must strengthen regulatory reforms, optimize the implementation of more transparent and integrated digital technologies, and ensure that decentralization operates in an accountable manner without creating opportunities for corrupt practices that hinder regional development. Keywords: Decentralization, corruption, local financial oversight, legal policy, e-budgeting, blockchain.